2006
DOI: 10.1007/s10877-006-9060-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new prototype hydrogel CO 2 sensor; comparison with air tonometry

Abstract: The hydrogel carbon dioxide sensor enabled fast and accurate pCO(2) measurement in a controlled environment but is very temperature dependent. The current prototype hydrogel sensor is still too unstable for clinical use, and should therefore be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…Finally, in a previous study by our group, three well-trained asymptomatic volunteers performed the same exercise protocol as used in this study. Their mean gastric gradient at maximum intensity exercise was 2.5 kPa, which is similar to the findings in the current study 16. Although our results show that after correction for difference in exercise intensity, the gastric and jejunal gradients of athletes with complaints during the exercise test exhibited a stronger increase per mmol/l lactate than those of athletes without symptoms, this was not statistically significant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, in a previous study by our group, three well-trained asymptomatic volunteers performed the same exercise protocol as used in this study. Their mean gastric gradient at maximum intensity exercise was 2.5 kPa, which is similar to the findings in the current study 16. Although our results show that after correction for difference in exercise intensity, the gastric and jejunal gradients of athletes with complaints during the exercise test exhibited a stronger increase per mmol/l lactate than those of athletes without symptoms, this was not statistically significant.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously shown that GI ischaemia occurs frequently during high-intensity exercise in asymptomatic subjects 15 16. In the current study, GI ischaemia was present in all subjects referred for exercise-induced GI symptoms, irrespective of whether or not their symptoms were provoked by our exercise test.…”
Section: Discussionsupporting
confidence: 52%
“…showed that a 10‐min exercise test to maximal intensity in healthy volunteers resulted in gastrointestinal ischaemia, but did not result in the development of GI‐symptoms . We confirmed these observations in healthy, well‐trained asymptomatic patients . Thus, although decreased GI blood flow is present in most people exercising at submaximal levels for 30 min or more, or at maximal levels for shorter times, the relation with development of GI‐complaints has not been established so far.…”
Section: Pathophysiology Of Changes In Splanchnic Blood Flow During Psupporting
confidence: 81%
“…While the results obtained by many researchers highlight the promising nature of hydrogels in biomedical sensors, work has yet to be done to demonstrate the ability of hydrogels to respond to small changes in pH and other analyte concentrations in solution. Some researchers have proposed utilizing hydrogel based sensors in implantable devices [7][8][9][10][11][12][13][14]. There are others who have focused on hydrogel-based sensors for use in measuring changes in systemic pH changes in the human body [9][10][11].…”
Section: Introductionmentioning
confidence: 99%